Penerapan Model Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII.1 SMP Negeri 23 Padang - firtinia, ullva; Suryani, Mulia; Hamdunah, Hamdunah (Universitas PGRI Sumatera Barat, 2021)
This research is motivated by the problems in class VIII SMP Negeri 23 Padang, it is known that the learning process is still centered on the teacher and students only accept learning from the teacher, and students have difficulty answering problem-solving questions given by the teacher. To overcome these problems, researchers used the Problem Based Learning (PBL). This Problem Basead Learning model can assist students in solving problem-solving problems given by the teacher. This type of research is a descriptive study, with a one shot case study design. Sampling was done based on purposive sampling, the sample was taken class VIII.1. The instrument used in this study was an essay test. The results of the study revealed that the students' mathematical problem-solving abilities taught by the Problem Based Learning (PBL) learning model were still below the completeness of the KKM set by the SMP Negeri 23 Padang school. So, it can be concluded that the application of the Problem Based Learning (PBL) model has not yet provided contribution to the learning success of students of SMP Negeri 23 Padang in grade VIII.1